Unsettling the reason of time: Indigenist epistemology and the child in the Australian curriculum. Issue 3 (4th May 2022) - Kelly, Stephen; Rigney, Lester-Irabinna
ABSTRACT: Colonial settler societies' differing concepts and experiences of time entangle in enactments of curriculum knowledge and the governing of human subjects. This article examines how an Anglo-Eurocentric historical representation of time is used as a principle of reason to establish the conditions of epistemic progress through the curriculum and culturally accounts for human agency, a teleological understanding of human development, and representations of the individual as a subject of knowledge. Here we question how representations of temporality are deployed in curricula to problematise human potential and the subjectification of individuals through the promise of securing human flourishing. We connect this discussion to the way people of the First Nations of Australia report their understanding of time as a principle to order an immanent experience of materiality, recurrence and becoming. This dialogue foregrounds how differing cultural conceptions of time establish conditions of possibility for experiencing and understanding the world.